Comparison of Vaginal Axis in Women Who Have Undergone Hysterectomy Versus Women With an Intact Uterus. Issue 4 (July 2019) - Lee, Daniel D.; Siegelman, Evan S.; Chua, Wynne Y.; Arya, Lily A.; Harvie, Heidi S.
Abstract : Objectives: To compare vaginal axis and posterior cul-de-sac measurements in women who have undergone hysterectomy and women with an intact uterus. Methods: This was a retrospective cohort study comparing magnetic resonance imaging findings in women who had undergone hysterectomy with women with an intact uterus. The primary outcome was change in the upper, middle, and lower vaginal axes relative to the pelvic inclination correction system line. Secondary outcomes included angles between the upper-middle and middle-lower vagina, depth of the posterior cul-de-sac, and total vaginal length. Results: In the hysterectomy group, the middle vaginal axis was significantly more anterior as compared with the intact uterus group (61.3 degrees ± 12.7 vs 49.4 degrees ± 23.6, P = 0.01). The upper-middle and the middle-lower vaginal angles were significantly more obtuse in the hysterectomy group than the intact uterus group (112.3 degrees ± 28.7 vs 69.3 degrees ± 56.6, P = 0.01 and 145.4 degrees ± 13.2 vs 130.9 degrees ± 29.7, P = 0.02, respectively). The mean depth of the posterior cul-de-sac and the total vaginal length were significantly shorter in the hysterectomy group than the intact uterus group (5.5 mm ± 7.6 vs 21.8 mm ± 11.9, P < 0.0001 and 78.7 mm ± 3.9 vs 100 mm ± 15.9, P < 0.001, respectively). Conclusions: The vaginal anatomy of women who have undergone hysterectomy differs significantly from that of women with an intact uterus.